CRIMINAL AND ADMINISTRATIVE ENFORCEMENT OF INDONESIA'S BAN ON THE IMPORTATION OF USED GOODS: AN ANALYSIS OF THE TRADE LAW FRAMEWORK FOLLOWING LAW NO. 6 OF 2023 AND MINISTER OF TRADE REGULATION NO. 47 OF 2025 - Munandar; Saut Parulian Panjaitan (Lex LATA, 2026)
The importation of used goods into Indonesia continues to pose legal and economic challenges despite the existence of statutory regulations prohibiting such activities. The persistence of these violations raises concerns regarding the effectiveness of criminal law enforcement under Law Number 7 of 2014 on Trade. This study aims to analyze the effectiveness of criminal law enforcement against the importation of used goods and to identify regulatory weaknesses that hinder effective enforcement. This research employs a normative legal research method using statutory, conceptual, and case approaches through the analysis of primary and secondary legal materials. The findings indicate that the existing criminal sanctions have not provided sufficient deterrence, particularly because the provisions in Articles 110, 111, and 112 paragraph (2) allow the imposition of imprisonment or fines as alternative sanctions. In addition, the absence of minimum criminal penalties and the limited application of administrative sanctions have reduced the effectiveness of law enforcement. Therefore, this study recommends revising the relevant provisions by replacing the phrase "and/or" with "and," introducing minimum criminal sanctions for imprisonment and fines, and strengthening the implementation of administrative sanctions. These measures are expected to enhance legal certainty, improve criminal law enforcement, and reduce cases of illegal importation of used goods.